2018
DOI: 10.1097/md.0000000000011104
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic assessment of carpal tunnel syndrome in diabetic patients with and without polyneuropathy

Abstract: The objective of this study is to determine whether the cross sectional area (CSA) measurement of the median nerve at the wrist differ between carpal tunnel syndrome (CTS) in diabetic patients with and without diabetic polyneuropathy (DPN).This study included 44 patients with type II diabete millitus (DM) with CTS, 32 patients with CTS and DPN, 46 patients with idiopathic CTS, and 42 healthy subjects. Ultrasonographic measurement of the CSA of the median nerve was made at the level of the wrist, together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
0
15
2
1
Order By: Relevance
“…6 ). In contrast to other authors 9 12 we propose that assessing CSA alone is insufficient for proper diagnosis of neuromatous change, since CSA was not increased in all examined neuromas (Fig. 7 ).…”
Section: Discussioncontrasting
confidence: 85%
“…6 ). In contrast to other authors 9 12 we propose that assessing CSA alone is insufficient for proper diagnosis of neuromatous change, since CSA was not increased in all examined neuromas (Fig. 7 ).…”
Section: Discussioncontrasting
confidence: 85%
“…In addition, treatment such as injection therapy can be conducted simultaneously with diagnosis, and adjacent structures can be evaluated if needed. A previous cross-sectional casecontrol study reported that the CSA of the median nerve of patients with CTS was similar to that of patients with CTS and DSP [ 21 ]. Another research study showed a similar result at the wrist level, but reported a significant difference in the CSA of the median nerve in the forearm level between patients with CTS only and those with CTS and DSP [ 16 ].…”
Section: Discussionmentioning
confidence: 93%
“…The presence of diabetic polyneuropathy has been shown to be associated with an increase in CSA of the median nerve at the carpal tunnel [ 16 , 31 ]. In contrast, others found median nerve CSA at the wrist significantly smaller in patients with CTS and diabetic polyneuropathy compared with diabetic patients with CTS only [ 15 , 43 ].…”
Section: Discussionmentioning
confidence: 98%